2015
DOI: 10.1089/ten.tec.2013.0725
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Neuronal Differentiation Toward Motor Neuron Lineage from Human Embryonic Stem Cell Line (H9)

Abstract: Motor neurons loss plays a pivotal role in the pathoetiology of various debilitating diseases such as, but not limited to, amyotrophic lateral sclerosis, primary lateral sclerosis, progressive muscular atrophy, progressive bulbar palsy, pseudobulbar palsy, and spinal muscular atrophy. However, advancement in motor neuron replacement therapy has been significantly constrained by the difficulties in large-scale production at a costeffective manner. Current methods to derive motor neuron heavily rely on biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Specifically, the high concentrations of iron, ferritin, and transferrin at birth indicate that a sufficient iron supply is closely related to normal neurological development [ 25 ]. Indeed, Lu et al demonstrated that elevated iron concentrations dramatically accelerated neuronal differentiation of ESCs through a transferrin-mediated mechanism [ 35 ]. Therefore, increasing iron concentration by incorporating iron-containing ferritin nanoparticles may also contribute to enhanced neuronal differentiation of NSCs and NPCs, but the exact mechanism requires further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the high concentrations of iron, ferritin, and transferrin at birth indicate that a sufficient iron supply is closely related to normal neurological development [ 25 ]. Indeed, Lu et al demonstrated that elevated iron concentrations dramatically accelerated neuronal differentiation of ESCs through a transferrin-mediated mechanism [ 35 ]. Therefore, increasing iron concentration by incorporating iron-containing ferritin nanoparticles may also contribute to enhanced neuronal differentiation of NSCs and NPCs, but the exact mechanism requires further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In hESCs treated with 500 nM iron, expression of the neuronal marker HB9 is doubled and the number of mature and functional motor neurons is 1.5 times higher than control. This is potentially mediated by the transferrin‐ferritin intracellular iron transport and storage mechanism . Iron is crucial for mitochondrial respiration serving as a cofactor of cytochrome and Fe sulfur complexes during oxidative phosphorylation .…”
Section: Micronutrients Enhance Neuronal Metabolism During the Differmentioning
confidence: 99%
“…In this regard transplantation therapy is employed to restore and repair the damaged circuitry of the brain as well as to replenish the lost neuronal population (Thompson and Björklund, 2015). Successful commitment of stem cells toward the neuronal lineage is widely reported and myriad of protocols are available to achieve the same (Nikoletopoulou and Tavernarakis, 2012; Ferroni et al, 2013; Lu et al, 2015). …”
Section: Stem Cells and Induced Pluripotent Stem Cells (Ipscs) In Neumentioning
confidence: 99%